Strategic IT–Business Alignment and Big Data Analytics Capability: A Configurational Approach to Operational Excellence in Manufacturing - Lukman (Indonesian Scientific Publication, 2025)
In the era of Industry 4.0, manufacturing firms face growing pressure to enhance operational performance through digital transformation. Central to this transformation is the strategic alignment between IT capabilities and business objectives, supported by advanced analytics and flexible IT infrastructures. This study investigates how different configurations of Strategic Alignment Maturity (SAMM), Big Data Analytics Capability (BDAC), IT flexibility, and business strategy types influence operational outcomes. Employing fuzzy set Qualitative Comparative Analysis (fsQCA) on data collected from 100 manufacturing firms, the research identifies multiple equifinal pathways to high operational performance, as measured by Overall Equipment Effectiveness (OEE) and SCOR metrics. Two dominant configurations emerge from the analysis. The first (R1) combines high levels of SAMM, IT flexibility, BDAC, and a Prospector strategy, highlighting a proactive, innovation oriented approach to operational excellence. The second configuration (R4) achieves similar performance through a different route leveraging BDAC, an Analyzer strategy, and strong CIO–business collaboration even in the absence of mature alignment structures. These results affirm that both alignment driven and analytics driven models can yield superior outcomes depending on organizational context and strategic orientation. The study contributes to the literature by demonstrating that high operational performance does not rely on a single universal model, but rather on the strategic orchestration of complementary capabilities. It also shows the effectiveness of fsQCA in uncovering complex causal relationships within organizational systems. Practically, the findings encourage manufacturing leaders to assess and tailor their alignment, analytics, and IT strategies according to their operational priorities and industry dynamics.